Pandangan Nadirsyah Hosen tentang Demokrasi dan Kepemimpinan - Ghifari, Muhammad Iqbal Akbar; Ubaidillah, Achmad; Huri, Daman (Department of Comparative Mazhab Comparative, Fakulty of Shariah and Law, 2022)
Abstract: This article discusses Nadirsyah Hosen's thoughts on democracy and leadership. This research is of the literature research type, and the data is analysed descriptively. The results of the study concluded that according to Nadirsyah Hosen, the democratic system is one way to return society to the Khilafah 'ala Minhaj an-nubuwwah (leadership based on what has been outlined by the Prophet). Regarding the requirements for leaders, Nadirsyah stated that leaders do not have to be from certain groups as long as they meet the requirements in accordance with the constitution of a country. If it is valid according to the constitution, it is also valid according to Islamic law. Nadirshah used maqashid as-shari'ah and the Intiqa'i method to determine statehood views. His opinion contributed to the reform of constitutional law in Islam. Keywords: Democracy, leadership, Islamic law, constitution. Abstrak: Artikel ini membahas tentang pemikiran Nadirsyah Hosen tentang demokrasi dan kepemimpinan. Penelitian ini berjenis Penelitian Pustaka dan data dianalisis secara deskriptif. Hasil Penelitian menyimpulkan bahwa menurut Nadirsyah Hosen sistem demokrasi merupakan salah satu cara untuk mengembalikan masyarakat kepada Khilafah ‘ala Minhaj an-nubuwwah (kepeminpinan berdasarkan apa yang telah digariskan oleh Nabi). Berkaitan dengan syarat pemimpin, Nadirsyah menyatakan bahwa pemimpin tidak harus dari golongan tertentu asalkan memenuhi syarat sesuai dengan konstitusi suatu negara. Jika sudah sah menurut konstitusi maka sah juga menurut hukum Islam. Nadirsyah menggunakan maqashid as-syari’ah dan metode Intiqa’i dalam menentukan padangannya mengenai ketatanegaraan. Pendapatnya tersebut memberikan kontribusi dalam pembaruan hukum ketatanegaraan dalam Islam. Kata Kunci: Demokrasi, kepemimpinan, hukum Islam, ketatanegaraan.